2017
DOI: 10.1093/police/pax031
|View full text |Cite
|
Sign up to set email alerts
|

Establishing and Maintaining Rapport in Investigative Interviews of Traumatized Victims: A Qualitative Study

Abstract: The study aim was to explore the factors considered important and useful in facilitating safety and building rapport in police investigative interviews with traumatized interviewees. We conducted 21 semi-structured interviews of police investigators involved in investigative interviewing of victims after the Utøya massacre on 22 July 2011 in Norway. Using a thematic analysis based on a reflexive hermeneutic-phenomenological epistemology, four themes emerged: (1) Preparation through planning, reflection, and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…The rationale for this research was twofold. First, the empirical literature is dominated by post-hoc investigations of rapport building (e.g., presence, absence, and likely impact) by accessing recordings or transcripts of real life interviews with witnesses and persons of interest [11,22,25,26,28,36,37], with relatively little attention paid to the impact of rapport behaviours on episodic memory performance. Second, because of the limited nature of experimental work that does consider episodic memory (e.g., verbal and behavioural techniques are often not separated), the locus of effect for rapport is far from clear and the results are somewhat contradictory (e.g., [16,18,20,[38][39][40]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale for this research was twofold. First, the empirical literature is dominated by post-hoc investigations of rapport building (e.g., presence, absence, and likely impact) by accessing recordings or transcripts of real life interviews with witnesses and persons of interest [11,22,25,26,28,36,37], with relatively little attention paid to the impact of rapport behaviours on episodic memory performance. Second, because of the limited nature of experimental work that does consider episodic memory (e.g., verbal and behavioural techniques are often not separated), the locus of effect for rapport is far from clear and the results are somewhat contradictory (e.g., [16,18,20,[38][39][40]).…”
Section: Discussionmentioning
confidence: 99%
“…Forensic interviews with witnesses are widely acknowledged as being socially and cognitively demanding and, in such contexts, effective communication is important. Here, key assumptions are centred on arguments that rapport has the potential to relieve some of the social demands of an interview, with a view to increasing capacity for cognitive processes such as episodic remembering [21][22][23][24][25][26]. Further, it has been argued that a comfortable witness may be more compliant [20,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the present study also highlighted the importance of active listening in helping them identify signs of distress. Research on police interviews after potentially traumatic events has shown that some police investigators are conscious of how distress can influence the interview process (Risan, Binder, & Milne, 2017). Participants also reported that they noticed that some interviewees' statements are disorganised.…”
Section: Active Listeningmentioning
confidence: 99%
“…I en klinisk setting er rapport tradisjonelt blitt beskrevet som viktigheten av å etablere en terapeutisk allianse (Webster, 2019, s. 14). I avhørsforskningen og -litteraturen har blant annet Risan et al (2018), Risan og Madsen (2019) samt Collins og Carthy (2019) referert til Tickle-Degnen og Rosenthal (1990) sitt teoretiske rammeverk. Tickle-Degnen og Rosenthal (1990) beskriver rapport som bestående av tre nonverbale komponenter, nemlig gjensidig «oppmerksomhet», «positivitet» og «koordinering».…”
Section: Empati Og Ivaretakelse I Avhørsforskningenunclassified